A disciplinarização do corpo feminino e a propriedade privada em “Senhor diretor”, de Lygia Fagundes Telles - Silva, Thayse Kelly Barbosa da (2020)
This thesis aims to analyze the short story “Senhor Diretor”, by Lygia Fagundes Telles. The work was published in the book of short stories “Seminário dos Ratos”, in the late seventies, more precisely in 1977, a period of history in which patriarchal values were still in force, despite the important behavioral changes that began to take place in Brazilian society in the twentieth century, due to political movements that questioned these values in respect to gender arrangements. Thus, our analysis presents as one of its main interests the discussion of these ideologies and how they affected women's lives. This is developed mainly through the analysis of main character, Maria Emília, a protagonist represented in a conflicting relationship with her body, disciplined by the impositions of patriarchy, and the anguish of being immersed in all these contradictions and determinations, even if unconsciously. Thus, we analyze how this ‘disciplinarization’ of the female body is understood as a historical factor, with its root in patriarchy, which, in turn, originated with the emergence of private property, making us think that the issue of women's oppression (be it financial, sexual, etc.), is directly related to class relations and the implied gender oppression. In addition, this analysis centers in the narrative text created by Lygia Fagundes Telles, bringing to light the theoretical support for this to take place properly. To support our research, we use some theoretical assumptions, such as those developed by Susana Borneo Funck (2011), Foucault (2006), Constância Lima Duarte (2003), Frederich Engels (1887), Mary Del Priore (2007), among others, in order to observe historical and cultural changes affecting the discussions on gender along last century.